2013
DOI: 10.1371/journal.pone.0058169
|View full text |Cite
|
Sign up to set email alerts
|

Concordant and Discordant Regulation of Target Genes by miR-31 and Its Isoforms

Abstract: It has been shown that imprecise cleavage of a primary or precursor RNA by Drosha or Dicer, respectively, may yield a group of microRNA (miRNA) variants designated as “isomiR”. Variations in the relative abundance of isoforms for a given miRNA among different species and different cell types beg the question whether these isomiRs might regulate target genes differentially. We compared the capacity of three miR-31 isoforms (miR-31-H, miR-31-P, and miR-31-M), which differ only slightly in their 5′- and/or 3′-end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Specifically, targets for the canonical miRNAs were compared with the targets of the miRNAs with seed regions shifted by −1, +1, and +2 nt. This analysis revealed that the number of predicted targets changed, but apart from unique targets, many genes were still predicted as targets for both miRNAs and isomiRs, confirming that isomiRs might share certain common mRNA targets but not all mRNA targets [36]. These results are also consistent with the suggestion that isomiRs function cooperatively to target common biological pathways [30].…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Specifically, targets for the canonical miRNAs were compared with the targets of the miRNAs with seed regions shifted by −1, +1, and +2 nt. This analysis revealed that the number of predicted targets changed, but apart from unique targets, many genes were still predicted as targets for both miRNAs and isomiRs, confirming that isomiRs might share certain common mRNA targets but not all mRNA targets [36]. These results are also consistent with the suggestion that isomiRs function cooperatively to target common biological pathways [30].…”
Section: Resultssupporting
confidence: 66%
“…Specifically, one variant of miR-101 [35] and two isomiRs of miR-133 [31] and miR-31 [36] have been investigated. In these reports, the isomiRs were less effective than their canonical analogs [35] or exhibited differences in effectiveness depending on the regulated target [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…File 10), which in turn suggests that in addition to the miRBase reference the isomiR variants can also be functionally active. One possible implication of this observation could be that the different isomiRs from the same precursor arm can work cooperatively to repress target genes or that they have slightly different targeting profiles that permit an increased diversity of the targeted transcripts [10, 20-22]. …”
Section: Discussionmentioning
confidence: 99%
“…The distribution of isomiRs indicates that they are not randomly generated, and may have (patho)physiological importance [56][58]. Indeed, specific isomiRs have been shown to be functional and to have target gene repertoires that differ from those of their corresponding canonical miRNAs [59], [60]. Recent data suggests the possibility of isomiR-specific gene targeting in the heart [61], [62].…”
Section: Introductionmentioning
confidence: 99%